Strong genomewide divergence between sympatric European river and brook lampreys - Mateus, Catarina Sofia (2013)
Lampreys, together with hagfishes, are the only extant representatives of jawless vertebrates and thus of prime interest for the study of vertebrate evolution [1]. Most lamprey genera occur in two forms with divergent life histories: a parasitic, anadromous and a non-parasitic, freshwater resident form [2-8]. The taxonomic status of such 'paired species' is disputed, however. While indistinguishable at larval stages, but clearly distinct as adults, they cannot be differentiated with available genetic data [6,7], which has fuelled speculations that the two forms may in fact represent products of phenotypic plasticity within a single species. Here, we use restriction site-associated DNA sequencing (RADseq) to examine the genetic population structure of sympatric European river (Lampetra fluviatilis L., 1758) and brook (Lampetra planeri Bloch, 1784) lampreys. We find strong genetic differentiation and identify numerous fixed and diagnostic single nucleotide polymorphisms (SNPs) between the two species, 12 of which can be unequivocally assigned to specific genes.